PEMBELAJARAN MUFRADAT MELALUI MEDIA DIGITAL UNTUK MAHASISWA - Fadli, Muhammad Fikri; Mufidah, Nuril; Agil, Idrus Muchsin Bin (Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study aims to describe 1. mufradat learning, 2. digital media, 3. mufradat learning strategies, 4. dynamics of problems faced by mabna ibn rusyd students when learning is done online through digital media. In this study, the authors used a qualitative descriptive methodology. This method uses data collection techniques carried out through observation, interviews, and documentation. The author found many findings related to mufradat learning in the Ma'had Sunan Ampel al-Aly environment related to learning methods using digital media. The results of this study indicate that mufradat learning through digital media at Mabna Ibn Rushd 6 applications are used to support online mufradat learning at Ma'had Sunan Ampel Al-Aly. 6 digital media applications are used in mufradat learning, namely, WhatsApp groups, PowerPoint, Kahoot, video conference zoom or google meet, infographics and animated videos from Canva and e-learning. There are four learning strategies used, 1. They write using a book and then send it through the WhatsApp group, 2. They are listening through audio-visual via video conference, 3. Animating videos via power point or Canva 4. Games through Kahoot as a form of evaluation of mufradat received by students. There are five problems faced by students in learning through digital media Network constraints, Boring, Lack of muraja'ah before receiving new mufradat, new Mufradat, and unstructured Mufradat (random).